Advocating for children with emotional and behavioral disorders: an interview with Eleanor Guetzloe - Kaff, Marilyn S.; Teagarden, James M.; Zabel, Robert H. (My University, 2014)
Eleanor Guetzloe shares her unique professional history in a conversation. Eleanor outlines her views on the history of the field and provides the reader with her insights on the future of the field. She offers valuable advice to those entering this field and shares what she sees as the areas where we can provide better support for children with challenging needs.
Keywords: Guetzloe, Eleanor; Emotional disorders; Behavioral disorders; Children; Advocacy